2020
DOI: 10.31092/jia.v4i2.735
|View full text |Cite
|
Sign up to set email alerts
|

Rural Development Policy and Poverty Alleviation: The Case of Village Funds in Aceh Province, Indonesia

Abstract: Village funds is still a new fiscal policy that was initially launched in 2015 by the seventh president of Indonesia, “Joko Widodo”, as his pilot project. Some villages have significantly benefited from developments and improvements initiated by the policy. However, it also has been identified through various investigative analysis that not all village funds allocations transferred to local governments have been implemented effectively and efficiently. This research examines the relationship between the villag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Every 1 percent addition to the village fund reduces poverty by 0.57% (Sari and Abdullah 2017). However, other findings have shown that the fund does not significantly reduce poverty (Azmi et al 2020;Sihite 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Every 1 percent addition to the village fund reduces poverty by 0.57% (Sari and Abdullah 2017). However, other findings have shown that the fund does not significantly reduce poverty (Azmi et al 2020;Sihite 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Di sisi lain, hasil penelitian ini mendukung temuan Sihite et al (2021), Imawan & Purwanto (2020) dan Azmi et al (2020) yang menyoroti peningkatan fasilitas infrastruktur perdesaan dari alokasi dana desa. Temuan ketiga studi tersebut menyatakan bahwa peningkatan fasilitas pelayanan publik dan infrastruktur belum maksimal sehingga belum signifikan berdampak pada upaya penanganan kemiskinan terutama di daerah perdesaan.…”
Section: Pembahasanunclassified